Variations in use of tertiary cardiac services in part of North-West England. - Gatrell, A; Lancaster, G; Chapple, A; Horsley, S; Smith, M (2002)
We assess the extent to which the need for tertiary cardiac care is being met uniformly within two Health Authorities in North-West England. We analyse small-area data from 1993-1996 on standardised rates of investigation (angiography) and surgery (bypass grafts and angioplasty). Utilisation by electoral ward is shown to be related to material deprivation. Small areas in which the Asian population is high have significantly fewer angiograms and angioplasties than might be expected according to need, while there is some evidence that women do not receive the levels of bypass surgery that might be expected.